The Legal Consequences Of The Decision Of The Constitutional Court Number 313/PHPU.BUP-XXIII/2025 On The Disqualification Of Candidates For Regent And Deputy Regent In The Regional Head Election Of Northern Barito District - Muklis Al'anam (CV. Akira Java Bulu, 2025)
Disqualification of regional head candidates is often a crucial issue in the dynamics of general elections. The decision of the Constitutional Court (MK) plays a central role in determining the validity of a nomination, including in cases of general election result disputes (PHPU). This article examines the legal implications of the Constitutional Court Decision Number 313/PHPU.BUP-XXIII/2025 regarding the disqualification of Regent and Deputy Regent candidates in the Regional Head Election (Pilkada) of North Barito Regency. This study uses a normative-legal method with a case study approach to the Constitutional Court's decision. The results of the analysis show that the Constitutional Court Decision Number 313/PHPU.BUP-XXIII/2025 has significant legal implications, both for the disqualified candidate pairs and for the implementation of subsequent Pilkada in North Barito Regency. This decision not only confirms the principles of justice and legal certainty in the election process, but also provides jurisprudential guidance for Bawaslu and KPU in following up on potential violations and nomination disputes.